A systematization of the literature on entrepreneurship education in higher education: challenges and emerging solutions in the entrepreneurial classroom - Naia, A.; Baptista, R.; Januário, C.; Trigo, V. (Industry and Higher Education, 2014)
This article reviews the literature on entrepreneurship education in the higher education context published over the first decade of the 2000s. The article has two purposes: to propose a framework of analysis to systematize and assess the literature; and to examine its main insights and contributions towards practice in the entrepreneurial classroom. The first decade of the 2000s is particularly relevant because it witnessed significant developments in the theoretical and empirical frameworks for the assessment of entrepreneurship education programmes and methodologies. The authors find that a very significant share of the research on entrepreneurship education over the period of analysis has sought to evaluate its results. There is not yet a consistent body of knowledge that can provide general insights and tools for practice. Practitioners need to pick and choose among pedagogical approaches and methods to select those that best suit their particular context.